Author Response: Progression of Nigrostriatal Denervation in Cerebellar Multiple System Atrophy: A Prospective Study. (14th June 2022) - Wirth, Thomas; Namer, Izzie Jacques; Monga, Ben; Bund, Caroline; Iosif, Andra; Gebus, Odile; Montaut, Solveig; Bogdan, Thomas; Robelin, Laura; Renaud, Mathilde; Kremer, Stéphane; Tranchant, Christine; et al.
Abstract : We thank Teive et al. for their valuable comments on our work. 1 We agree that REM sleep behavior disorders (RBD) are a typical hallmark of α-synucleinopathies, including multiple system atrophy (MSA). 2 Some pieces of evidence suggest that RBD could be useful in differentiating idiopathic late-onset cerebellar ataxia (ILOCA) from cerebellar MSA (MSA-C). 3 It has also been shown that RBD could predate the onset of cerebellar syndrome in MSA-C; for this reason, it has recently been suggested to create a criteria set for possible prodromal MSA-C defined by the association of RBD with cerebellar ataxia. 4